A new model of the personnel function delivery in the logistics of Polish firms - Elżbieta Gołembska; Marcin Gołembski (Logistics, 2020)
In the article, a new phenomenon of global logistification provides a context for presenting the newest trends in the development of HR management and its role in logistics. The new trends include a growing internationalization of firms, combined flows of capital, people and technical knowledge, and the issue of key logistics competences. Against this background, the article describes a new model of the HR management function in logistics. The aim is to find the relationship between designing and delivering the personnel function in a firm and the effectiveness of logistics management. The key aspects of the personnel function management include talent and competencies management, personnel risk management, and employer branding. These HR practices are explored to determine attributes of the personnel function, and to describe challenges of the proactive human resource management in logistics. The article continues with a presentation of the results of empirical studies conducted in the period 2017-2018 of 236 large, medium-sized, and small Polish firms. As the primary methods, the research used a diagnostic survey, a questionnaire, and the statistical method of factor analysis. The second part of the article presents an original model of the personnel function in logistics management, with regard to the specificity of Polish firms. The findings based on the study results refer to both the present and future status of HR management in logistics. The main findings of the studies acknowledge the influence of all-embracing logistification on the volumes and structure of knowledge transfer in supply chains, and reveal a growing decentralization of HR management in large and medium-sized companies, resulting in an imbalance between the levels of personnel function implementation in large and medium-sized companies, compared with small firms.
Keywords: 650; logistification; personnel function; logistics management; talent management; HR attributes; flow of capital; knowledge and people; employer branding